Shaping emotional reactions to ethical behaviors: Proactive personality as a substitute for ethical leadership - Velez, M. J.; Neves, P. (Leadership Quarterly, 2018)
Due to ethical lapses of leaders, interest in ethical leadership has grown, raising important questions about the responsibility of leaders in ensuring moral and ethical conduct. However, research on ethical leadership has failed to examine the active role that followers' attributes play in enhancing or minimizing the influence of ethical leadership in organizational outcomes. We applied the substitutes for leadership approach (Kerr & Jermier, 1978) to ethical leadership and predicted that proactive personality acts as substitute in the relationship between ethical leadership, workplace emotions and organizational citizenship behaviors (OCBs). Data from two distinct samples offered strong support for the hypotheses. Specifically, we found that ethical leadership was significantly and negatively related to negative workplace emotions when subordinate proactive personality was low, but not when it was high, with consequences for OCBs. These findings suggest that proactive personality constitutes an important moderator on the impact of low ethical leadership on workplace emotions, with consequences for OCBs.